Understanding the Venezuelan Crisis: Origins and Current Situation (2021)
The aim of this paper is to present the origins and development of the current crisis in Venezuela and analyse the future implications of relations between the de facto government of Nicolas Maduro, the United States, Russia, China, Cuba, and Middle Eastern Countries. All indications are that the situation in Venezuela cannot be resolved in the near future, unless the governments of Russia, China, Cuba, Iran, and the U.S., together with the government of the interim president of Venezuela and the de facto government of Nicolas Maduro, reach an agreement to create a transitional government and hold free and transparent elections.